2017
DOI: 10.1111/ejh.12963
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic impact of anemia and iron deficiency in patients hospitalized in an internal medicine ward: The PROIRON study

Abstract: Anemia and iron deficiency were highly prevalent in internal medicine patients. As anemia negatively impacts on in-hospital mortality, awareness should be raised for effective diagnosis and management of these comorbidities in hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
(55 reference statements)
4
9
0
Order By: Relevance
“…Our hospital-based study provides further support to these data, as our observations are in line with the percentage of anemia in geriatric patients as reported in other hospital-based studies [27], confirms the high prevalence of anemia in hospitalized patients [28][29][30][31] and its impact on the duration of hospital stay, on the number of re-admissions and, ultimately, on mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Our hospital-based study provides further support to these data, as our observations are in line with the percentage of anemia in geriatric patients as reported in other hospital-based studies [27], confirms the high prevalence of anemia in hospitalized patients [28][29][30][31] and its impact on the duration of hospital stay, on the number of re-admissions and, ultimately, on mortality.…”
Section: Discussionsupporting
confidence: 91%
“…We report a high prevalence of ID and anemia in real-world HF patients, similar to previous reports [1,2,[18][19][20]. The combination of anemia and ID was around 30% in patients across all ranges of LVEF.…”
Section: Discussionsupporting
confidence: 89%
“…Current guidelines recognize ID and anemia as important comorbidities in patients with HF [12,13]. Although in some cohorts with a higher prevalence of HF with preserved ejection fraction, ID is not associated with worse prognosis when adjusting for anemia and other comorbidities [5,[18][19][20], ID is associated with worse functional capacity and quality of life across all ranges of LVEF [3][4][5].…”
Section: Treatment Of Patients With Id And/or Anemiamentioning
confidence: 99%
“…However, compliance with recommended oral iron intake among pregnant women varies, mostly due to the gastrointestinal side effects. Multivitamin and mineral compounds are not the best way for supplementation, mainly when ID or IDA is present, as most of them do not contain adequate amounts of iron, vitamin B 12 , C or D. Indeed, the EMPIRE study in Portugal found that IDA had a very high prevalence among pregnant women (54.2%), despite the fact that over 80% of them were receiving iron supplementation, mostly administered as multivitamin and mineral products [59].…”
Section: Sucrosomial® Iron For the Management Of Iron Deficiency Imentioning
confidence: 99%